Navigating Recurrent Corneal Injury: Addressing Challenges in Lawnmower-Related Ocular Trauma - Rokim, Fitri Setyani; Kusumastuti, Fitria; Surakhman, Budy (Vision Science and Eye Health Journal, 2025)
Introduction: Ocular trauma resulting from workplace accidents, such as those involving lawnmowers, can cause severe eye injuries, potentially leading to significant visual impairment. Case Presentation: A 42-year-old male presented with sudden vision loss, redness, and pain in the right eye following a workplace accident. Examination revealed a full-thickness corneal laceration, hyphema, and anterior chamber prolapse of the iris and vitreous. The patient underwent a surgical repair. However, recurrent injuries necessitated additional intervention, ultimately resulting in a corneal leucoma. Although postoperative symptoms initially improved, wound dehiscence led to recurrent vitreous leakage, complicating recovery. This case highlights the challenges associated with managing recurrent corneal injuries and underscores the importance of precise surgical techniques to optimize outcomes. Conclusion: This case emphasizes the complexity of recurrent ocular trauma, particularly in workplace-related injuries such as lawnmower accidents. A comprehensive patient history, individualized management approach, and multidisciplinary collaboration are essential for improving visual prognosis and surgical success.